UV-curing and thermal ageing of methacrylated stereo-lithographic resin. (March 2021) - Marin, Elia; Boschetto, Francesco; Zanocco, Matteo; Doan, Hoan Ngoc; Sunthar, Thefye P.M.; Kinashi, Kenji; Iba, Daisuke; Zhu, Wenliang; Pezzotti, Giuseppe
Highlights: Resin degradation and curing could be correlated with spectroscopic parameters. Curing parameters could be optimized (temperature/time) to maximize mechanical properties. Thermal cycling was successfully used to simulate aging. An algorithm could be obtained by correlating spectroscopic parameters and mechanical properties. Abstract: 3D printing is nowadays a consolidated standard for the manufacturing of various polymeric materials. Stereography, in particular, has seen an ever-growing industrial interest due to the high precision and the flexibility. Methacrylated resins are a common, inexpensive choice for high resolution additive manufacturing, but their mechanical properties are strongly influenced by oxidation and thermal cycling. In this work, samples produced with a commercially available methacrylated resin were UV-post cured at different conditions and then artificially aged using a low/high temperature step cycle. Ageing affected the ultimate strength of all samples, but the UV post-curing effectively reduce the loss. Spectroscopic analysis confirmed that the UV post-curing at moderate temperature increased the degree of chain cross-linking, while the artificial ageing and curing at high temperatures induced oxidation and brittleness.